2022
DOI: 10.3390/cancers14235939
|View full text |Cite
|
Sign up to set email alerts
|

Collagen-Based Biomimetic Systems to Study the Biophysical Tumour Microenvironment

Abstract: The extracellular matrix (ECM) is a pericellular network of proteins and other molecules that provides mechanical support to organs and tissues. ECM biophysical properties such as topography, elasticity and porosity strongly influence cell proliferation, differentiation and migration. The cell’s perception of the biophysical microenvironment (mechanosensing) leads to altered gene expression or contractility status (mechanotransduction). Mechanosensing and mechanotransduction have profound implications in both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 150 publications
(162 reference statements)
0
0
0
Order By: Relevance
“…The authors of [2] found that the 3D ECM geometry influenced the number, length, and organization of TNTs and that TNTs interact with the ECM in a suspended nanofiber network. To conclude this topic, Cambi and Ventre [3] published a review discussing the importance of collagen in the ECM and the types of ECM biomimetic scaffold that are available for in vitro research.…”
mentioning
confidence: 99%
“…The authors of [2] found that the 3D ECM geometry influenced the number, length, and organization of TNTs and that TNTs interact with the ECM in a suspended nanofiber network. To conclude this topic, Cambi and Ventre [3] published a review discussing the importance of collagen in the ECM and the types of ECM biomimetic scaffold that are available for in vitro research.…”
mentioning
confidence: 99%